AN ENQUIRY INTO THE INFORMATION RETRIEVAL EFFICIENCY OF LISA PLUS DATABASE - Sen, Bimal Kanti; Sen, B. K. (Malaysian Journal of Library and Information Science, 2017)
Tests the information retrieval efficiency of LISA Plus database in retrieving the abstracts of articles on the library profession published in Asian library and information science journals from the aforementioned database by employing two dif-ferent methods of computerised searches and a manual search. The manual search from LISA (printed version of LISA Plus) retrieved 73 articles in 26 minutes, whereas the computerised searches retrieved 42 and 19 articles in 90 and 41 minutes respectively. Examines the reasons why computerized searches took more time and retrieved less number of items. Suggests measures whereby the efficiency of compu-terised searches can be increased and concludes that to ensure comprehensive recall of relevant items, a combination of manual and computerised search is indispensable.